Development of physico-mathematical model and justification of parameters of device for air cooling by dropping water - Тишин, Роман Александрович; Толкунов, Игорь Александрович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper deals with solving actual scientific and technical task to ensure safe working conditions for personnel in workplaces of industries with high temperatures (over 300 °C), such as deep mine workings, blast furnace shops, etc., which lies in a local air cooling without using special conditioners, where the greatest effect is achieved in the processes of hydrodynamic irrigation of warm air by dropping water. It is shown that the measures, aimed at reducing the air temperature of working areas in mine workings involve air cooling by forced ventilation and air conditioning systems, which do not fully meet the required quality parameters. This has a negative effect on the overall condition of personnel and enterprise efficiency as a whole, and causes the risk of diseases from overheating respiratory organs and dehydration. Solving the problem of physico-mathematical modeling of the dispersed water impact on the air and heat exchange occurring between droplets and air is urgent for improving the irrigation-based mine air cooling effect. The design of the device for the hydrodynamic air cooling by dropping water based on diffuser-confuser pipe was developed, and relations that allow to determine the structural and operational parameters were defined. The analytical relations, the appropriateness of which was experimentally confirmed reveal the mechanism of cooling action of water droplets on the air, enable the analytical determination of the thermodynamic characteristics of the flow, which affect the heat transfer efficiency, and justification of means, required for this process. Using the developed device in workplaces of industries with high temperatures will ensure the implementation of labor protection requirements on air quality in working areas, as well as high efficiency of air cooling measures, which is caused by the possibility of engineering calculations when designing the proposed devices.